Nature-Based Islamic Religious Education (PAI) through the Pondok Salam Qur’an Program in Shaping Students’ Religious Character - Bilqis Nafilah Febrianti; Agus Fakhruddin; Usup Romli (UIN Sultan Aji Muhammad Idris Samarinda, 2026)
Abstract The purpose of this study is to analyze the strategy of nature-based Islamic Religious Education (PAI) learning through the Pondok Salam Qur’an (PSQ) program in shaping students’ religious character at Sekolah Alam Bogor. PAI learning faces challenges in the era of globalization and digitalization, particularly the dominance of cognitively oriented, rote-memorization approaches that are less effective in internalizing religious values. This study employed a qualitative approach with a case study design. Data were collected through in-depth interviews, observations, and document reviews involving PAI teachers, students, PSQ mentors, and parents. The data were analyzed using Miles and Huberman’s interactive model, which includes data reduction, data display, and conclusion drawing. The findings indicate that nature-based PAI learning through the PSQ program provides contextual learning experiences that support the formation of students’ religious character through worship habituation, Qur’anic activities, and interaction with the environment. Despite challenges such as managing open-space classes and digital distractions, this strategy remains effective in strengthening students’ spiritual appreciation and sustaining religious habits. Keywords: Islamic Religious Education (PAI), nature-based learning, religious character, PSQ